que Fusi es para la historiografía española - Ugarte Tellería, Javier (Huarte de San Juan. Geografía e Historia, 2015)
On the occasion of his retirement from the Complutense University of Madrid and his promotion to the status of Emeritus Professor thereof, this article reviews the professional life of Juan Pablo Fusi Aizpurúa and stresses his relevance for historiography and, more generally, for the Spanish and Basque public life. The review starts from the years at the University of Oxford as a post-graduated Ph D student, and proceed to analyze the «critical revisionism» of his historiography derived from British empiricism (Lewis B. Namier, Trevor-Roper...) as Isaiah Berlin explained it. Finally the article analyzes Fusi’s historiographical production and his public institutional biography and academic responsibilities, according to an askesis and spirit of service that resembled that of the Spanish philosopher José Ortega y Gasset.